REALISASI STRATEGI KESOPANAN DALAM TINDAK TUTUR DIREKTIF PADA FILM KUNGFU PANDA - Sufil Lailiyah; Nine Febrie Novitasari (CERMIN: Jurnal Penelitian, 2018)
This research is pragmatic study which has a purpose to describe politeness strategies of directive speech act in Kungfu Panda movie. That movie has been watching by people including children.Therefore the use of language in that movie being an interesting matter to be analyzed. The politeness theory proposed by Brown & Levinson used to describe politeness strategy of directive utterances in Kungfu Panda movie. This research uses descriptive qualitative approach. Some methods used in this study are: first, the data are collected by using observation method. Second, the data are analyzed using Sparadley’s theory by making domain analysis, taxonomic analysis, componential analysis, and discovering cultural themes. Third, in presenting the result of data analysis uses an informal method of presentation. The result of this research showes that there are fifty four directive utterances which use politeness strategy, both positive politeness strategy and negative politeness. Positive politeness strategy used by (1) using in-group identity markers, (2) being optimistic, (3) including both speaker and hearer in the activity, (4) giving sympathy to hearer. Negative politeness strategy used by (1) being conventionally indirect, (2) being pessimistic, (3) minimising the imposition, (4) giving deference, (5) impersonalizing speaker and hearer, and the last (6) stating face threatening act as a general rule.